User Involvement in Myasthenia Gravis Research - Gilhus, Nils Erik; Hovland, Sandra Iren Barkås (Frontiers in Neurology, 2022)
More and better research is needed for myasthenia gravis (MG). Partnership with patients as user representatives in MG research groups will strengthen their research. User representatives are especially important in the project planning phase, in recruitment of patients, in the assessment of the results, for dissemination, and for implementation. For funding applications, user involvement is often requested. The needs for MG patients are disease-specific, and user representatives should therefore have active MG. The focus of the research group should be considered when recruiting a patient representative. User representatives give direct advice, use their personal MG experience, convey input from their MG network, include their professional education and work experience, and sometimes take the role of the concerned citizen. They are especially important as partners in guideline documents and policy papers. Both researchers and user representatives need to reflect on their position in the partnership.